IL-10 Gene polymorphism and graft outcome in live-donor kidney transplantation - Rashad, Rashad Hassan; Mahmoud, Khaled Mohamed; El-Agroudy, Amgad El-Baz; Hamdy, Ahmed Farouk; Ismail, Amani Mostafa; Sayed, Nagy Abd-El Hady; Sobh, Mohamed Abd El-Kader (African Journal of Nephrology, 2017)
Background: The description of polymorphisms in many of the key immunoregulatory molecules involved in the rejection process has offered a possible explanation for the individual variation in susceptibility to rejection and differences in allograft survival independent of the many known contributory factors. The aim of this work is to study the impact of IL-10 cytokine gene polymorphism on renal transplant clinical course and outcome. Methods: This work studied 50 transplant recipients maintained on sirolimus based immunosuppression for IL-10 cytokine gene polymorphisms. After transplantation patients were divided into two groups. Group (A) patients (12 patients) received sirolimus, tacrolimus and steroid, while Group (B) patients (38 patients) received sirolimus, mycophenolate mofetil and steroid. Results were correlated with acute and chronic rejection episodes as well as graft and patient outcome. Results: In our study, we found no impact of IL-10 on incidence and degree of acute rejection episodes, incidence of chronic allograft nephropathy, pathological changes in protocol biopsies, graft function and graft and patient survivals. Conclusion: From this work, we can conclude that the potential impact of IL-10 cytokine gene polymorphisms on renal transplant clinical course and outcome have shown no influence, and probably other genes rather than IL-10 could be involved as key molecules for graft function.